Two new lignans with their biological activities in Portulaca oleracea L. (August 2022) - Wang, Chengyu; Guo, Shengnan; Tian, Jiayin; Liu, Peishan; Song, Mingyang; Zhang, Wenjie; Ying, Xixiang
Abstract: Two new lignans, identified as 6, 7-dihydroxy-4-(4′'-hydroxy-3′'-methoxyphenyl)-2-naphthoic acid, named Oleralignan C (1 ), and 4-(3, 4-dihydroxyphenyl)-6-hydroxy-7-methoxy-2-naphthoic acid, named Oleralignan D (2 ), were obtained from Portulaca oleracea L. The structures were determined by spectroscopic methods, including UHPLC-ESI-QTOFMS, 1 D and 2 D NMR. Both Oleralignan C (1 ) and Oleralignan D (2 ) inhibited the inflammatory factors, IL-1 β and TNF- α in RAW 264.7 cells induced by lipopolysaccharide (LPS). Both compounds also could clear 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) radicals indicating their antioxidant potential. Graphical Abstract: ga1 Highlights: Two new lignans were isolated from Portulaca oleracea L. The two lignans exhibited remarkable anti-inflammatory and antioxidant bioactivities. 3. Our findings provide a novel therapeutic potential for Alzheimer's disease.